2013
DOI: 10.1111/and.12175
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Pumpkin seed extract on sperm characteristics, biochemical parameters and epididymal histology in adult male rats treated with Cyclophosphamide

Abstract: Cancer treatment with cyclophosphamide (CP) may result in reproductive toxicity as one of its side effects. The pumpkin seed is a rich natural source of antioxidant. We have assessed the possible protective efficacy of pumpkin seed extract on sperm characteristics, biochemical parameters and epididymal histology of CP-treated rats. Male adult Wistar rats were categorised into four groups. Group 1 served as control and received intraperitoneal (IP) injection of isotonic saline solution. Group 2 rats were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 41 publications
(56 reference statements)
3
12
0
2
Order By: Relevance
“…Sakr & Nooh (2013) who studied the effect of Ocimum basilicum extract on cadmium-induced diabetes detected an improvement in testes tissue such as mean tubular diameter and germ cell height that attributed to the antioxidant properties of the plant (Sakr & Nooh). Aghaei et al (2014) demonstrated the effect of pumpkin seed extract in cyclophosphamide-treated rats. Vacuolization, disorganization, and separation of epididymal epithelium improved remarkably following the administration of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Sakr & Nooh (2013) who studied the effect of Ocimum basilicum extract on cadmium-induced diabetes detected an improvement in testes tissue such as mean tubular diameter and germ cell height that attributed to the antioxidant properties of the plant (Sakr & Nooh). Aghaei et al (2014) demonstrated the effect of pumpkin seed extract in cyclophosphamide-treated rats. Vacuolization, disorganization, and separation of epididymal epithelium improved remarkably following the administration of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…CP is widely used as an anti-cancer agent, which, however, can cause several adverse effects including reproductive toxicity, since it can inhibit proliferation of cells on account of its DNA-damaging effect (Tripathi and Jena, 2008). Although reports on CP-induced reproductive toxicity are available, little is known about the mechanisms (Kim et al, 2012;Aghaei et al, 2014;Comish et al, 2014). In our study, we have discovered that CP can cause a noticeable decrease in serum testosterone level and increase the apoptotic rate in the testis, thus giving rise to a decline in spermatozoon motility and viability and leading to infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of doses and dosing schedule as shown in Figure , for nerolidol and cyclophosphamide, was based on the earlier published reports (Aghaei et al, ; Iqubal, Sharma, Najmi, et al, ). Animals were randomly divided into five groups ( n = 6) and treated as shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Selection of doses and dosing schedule as shown in Figure 1, for nerolidol and cyclophosphamide, was based on the earlier published reports (Aghaei et al, 2014;.…”
Section: Treatment Protocolmentioning
confidence: 99%